Short Dental Implants: An Umbrella Review of Current Systematic Reviews and Meta-analysis on Survival Rate of Short Dental Implants - Ramezanzade, Shaqayeq; Tuminelli, Frank; Marques, Duarte; Keyhan, Seied Omid; Yousefi, Parisa; Lopez-Lopez, Jose (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: This study aimed to report on systematic reviews assessing the survival/failure rate of short implants. Additionally, marginal bone loss (MBL) and factors affecting survival rates was assessed. Materials and Methods: PubMed-Medline, Google Scholar, Latin American and Caribbean Health Sciences Literature (LILACS) and the Cochrane Database of Systematic Reviews were searched up to January 2020. Also reference lists of included systematic reviews were hand-searched. The AMSTAR tool was used for quality assessment. Results: 659 studies were reviewed and 37 studies (25 metanalysis) were included. According to the AMSTAR tool, 19 of the 37 reviews were classified as high, 13 as medium and 5 as low quality. The mean score (±SD) was 7.10 (±2.74). The survival rate reported in studies varied from 84% to 100% for follow up periods of 1-5 years (more than 80% of included studies had a minimum follow-up period of 1-5 years), while failure rates ranged from 0% to 37.5% (the same as survival rate range from 62.5% to 100%). Included Systematic reviews reported no significant difference between survival rate/failure of Short implants (SIs) and standard implants with bone augmentation. Two high-quality metanalysis revealed a statistically significant lower survival rate for SIs as well as 2 systematic reviews which found SIs had significantly increased failures. Surface characteristics and implant location showed some association with survival rate. In some studies, SIs experienced lower MBL than standard implants while in others no differences were observed. Conclusion: Current knowledge from systematic reviews demonstrated acceptable survival rates for SIs. No significant difference between survival rate/failure of SIs and standard implants with bone augmentation was reported in the majority of studies. Systematic review registration number: PROSPERO Number: CRD42020163931.